Form for reporting Iowa Christmas bird counts to Iowa Bird Life, Sharon Kaufman, December 18, 1987 - Kaufman, Sharonet al (1987)
Iowa Christmas bird counts of regular and uncommon species found in Lost Nation contributed by Sharon Kaufman, December 18, 1987. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of winter 1987-1988. Epson - sheet feed